1997
DOI: 10.1177/002221949703000603
|View full text |Cite
|
Sign up to set email alerts
|

State Disparities in the Diagnosis and Placement of Pupils with Learning Disabilities

Abstract: We investigated the hypothesis that interstate disparities in the diagnosis of pupils with learning disabilities (LD) are more strongly correlated with demographic and sociopolitical factors than with the biological prevalence of the disability. We also investigated the relationship of these factors to placement practices. Thirteen independent variables representing state characteristics were simultaneously regressed against each of seven static dependent variables, measuring diagnostic and placement practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…Although schools are under increasing pressure to incorporate evidence-based interventions to meet the diverse needs of children with autism (Lester & Kelman, 1997), few evidence-based programs have been adopted or successfully implemented in schools. Though social engagement interventions may have the most meaningful results for children with autism if implemented in schools (Locke, Kasari, Rotheram-Fuller, Kretzmann, & Jacobs, 2013), the complexity of these interventions makes them difficult to implement in public schools, given the limited resources and training often available (Dingfelder & Mandell, 2011).…”
mentioning
confidence: 99%
“…Although schools are under increasing pressure to incorporate evidence-based interventions to meet the diverse needs of children with autism (Lester & Kelman, 1997), few evidence-based programs have been adopted or successfully implemented in schools. Though social engagement interventions may have the most meaningful results for children with autism if implemented in schools (Locke, Kasari, Rotheram-Fuller, Kretzmann, & Jacobs, 2013), the complexity of these interventions makes them difficult to implement in public schools, given the limited resources and training often available (Dingfelder & Mandell, 2011).…”
mentioning
confidence: 99%
“…The number of children with autism served in public schools has increased dramatically within the last decade (Blumberg et al, 2013), making the improvement of school-based autism services a national priority in the United States (US; Lester & Kelman, 1997; Locke, Kratz, Reisinger, & Mandell, 2014). In the US, the Individuals with Disabilities Education Act (IDEA, 2004) and the No Child Left Behind Act of 2001 (NCLB, 2002) require that school systems implement “scientifically based” (i.e., evidence-based) educational and behavioral practices.…”
mentioning
confidence: 99%
“…The few published studies of the effects of policy variation on service delivery have found that education policies and level of aide for children with disabilities are highly predictive of the proportion of identified learning disabilities (Cullen, 2003;Lester & Kelman, 1997). A number of other studies have found that state of residence is a more powerful predictor of specialty service use than demographics and perceived need among children with developmental and psychiatric disabilities (Cox, Motheral, Henderson, & Mager 2003;Hoagwood, Jensen, Feil, Vitello, & Bhatara, 2000;Long & Coughlin, 2001;Stevens, Harman, & Kelleher, 2004;Sturm, Ringel, & Andreyeva, 2003;Szilagyi et al, 2003;Zito et al, 1999Zito et al, , 2003Zito, Safer, dosReis, & Riddle, 1998).…”
mentioning
confidence: 99%